Utilizing Ion Mobility-Mass Spectrometry to Investigate the Unfolding Pathway of Cu/Zn Superoxide Dismutase - Butler, Karen E.; Takinami, Yoshihiko; Rainczuk, Adam; Baker, Erin S.; Roberts, Blaine R. (Frontiers in Chemistry, 2021)
Native mass spectrometry has emerged as a powerful tool for structural biology as it enables the evaluation of molecules as they occur in their physiological conditions. Ion mobility spectrometry-mass spectrometry (IMS-MS) has shown essential in these analyses as it allows the measurement of the shape of a molecule, denoted as its collision cross section (CCS). The structural information garnered from native IMS-MS provides insight into the tertiary and quaternary structure of proteins and can be used to validate NMR or crystallographic X-ray structures. Additionally, due to the rapid nature (millisecond measurements) and ability of IMS-MS to analyze heterogenous solutions, it can be used to address structural questions not possible with traditional structural approaches. Herein, we applied multiple solution conditions to systematically denature bovine Cu/Zn-superoxide dismutase (SOD1) and assess its unfolding pathway from the holo-dimer to the holo-monomer, single-metal monomer, and apo-monomer. Additionally, we compared and noted 1-2% agreement between CCS values from both drift tube IMS and trapped IMS for the SOD1 holo-monomer and holo-dimer. The observed CCS values were in excellent agreement with computational CCS values predicted from the homo-dimer crystal structure, showcasing the ability to use both IMS-MS platforms to provide valuable structural information for molecular modelling of protein interactions and structural assessments.